Quality Of Sausage Incorporated With Chicken Liver As A Source Of Iron (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Iron is an important micronutrient for the body and its deficiency causes anemia. Its bioavailability is higher in foods of animal origin such as meat and liver. Chicken and beef liver are the most used in human food and are consumed in various preparations such as spreadable pâté or sausages. The purpose of this study was to evaluate the quality of sausage incorporated with chicken liver as a source of iron. Three sausage formulations were made, each with 40% chicken liver and 40% meat ingredient that varied according to the formulation: chicken liver with chicken meat (HPCP), chicken liver with beef (HPCR), and chicken liver with pork (HPCC). The sensory acceptance of the formulations in their attributes of color, odor, taste, texture, and global impression was evaluated to determine the physicochemical (moisture, proteins, fats, iron) and microbiological characteristics in the formulation with the highest acceptance. The highest scores in sensory attributes were obtained in the HPCC formulation, which was characterized by being an excellent source of iron (6.52 mg/100 g) and an excellent source of protein (21.19%) according to the daily nutritional reference value for children over 4 years of age and adults established in Resolution 810 of 2021 in Colombia. The product had a good microbiological quality, which indicates adequate heat treatment. In this sense, sausage with chicken liver and pork represents an alternative to iron consumption.
Keywords: chicken liver; Iron; meat industry; Sausage